2022
DOI: 10.1002/jgt.22920
|View full text |Cite
|
Sign up to set email alerts
|

On coloring digraphs with forbidden induced subgraphs

Abstract: We prove a conjecture by Aboulker, Charbit, and Naserasr by showing that every oriented graph in which the out-neighborhood of every vertex induces a transitive tournament can be partitioned into two acyclic induced subdigraphs. We prove multiple extensions of this result to larger classes of digraphs defined by a finite list of forbidden induced subdigraphs. We thereby resolve several special cases of an extension of the famous Gyárfás-Sumner conjecture to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…In this paper, we show that every orientation of P 4 is − → χ -bounding and thus the ACN − → χ -boundedness conjecture holds for all orientations of Our result also answers the question of [25] in the affirmative, that is, for H ∈ { − → P 4 , − → A 4 } and any k 4 the class of H-free oriented graphs not containing a transitive tournament of order k has bounded dichromatic number.…”
Section: Our Contributionssupporting
confidence: 58%
See 1 more Smart Citation
“…In this paper, we show that every orientation of P 4 is − → χ -bounding and thus the ACN − → χ -boundedness conjecture holds for all orientations of Our result also answers the question of [25] in the affirmative, that is, for H ∈ { − → P 4 , − → A 4 } and any k 4 the class of H-free oriented graphs not containing a transitive tournament of order k has bounded dichromatic number.…”
Section: Our Contributionssupporting
confidence: 58%
“…− → K t denote the transitive tournament on t vertices. In [25], Steiner showed that the class of ( − → K 3 , − → A 4 )-free oriented graphs has bounded dichromatic number. In the same paper Steiner asked whether the class of (H, − → K t )-free oriented graphs has bounded dichromatic number for t 4 and…”
Section: • Letmentioning
confidence: 99%
“…In [14] it is proved that it is enough to prove the conjecture for trees, the conjecture has been proved to be true for oriented stars [8].…”
Section: Growing a Heromentioning
confidence: 99%
“…As said in Section 5.1, it is proved in [8] that for every oriented star F , all transitive tournaments are heroes in Forb F ( ) ind . The only other known result so far is concerned with ⎯→ ⎯ K 1,2 (the oriented star on three vertices, with one vertex of out-degree 2 and two vertices of in-degree 1): it is proved in [1,14]…”
Section: Heroes In Forb F ( )mentioning
confidence: 99%
See 1 more Smart Citation